DFT calculation of the potential energy landscape topology and Raman spectra of type I CH4 and CO2 hydrates. Issue 10 (13th February 2015) - Vidal-Vidal, Ángel; Pérez-Rodríguez, Martín; Torré, Jean-Philippe; Piñeiro, Manuel M.
Abstract : Type I methane and carbon dioxide hydrates analyzed using DFT calculations: Raman spectra and potential energy landscape. Abstract : CO2 and CH4 clathrate hydrates of type I were studied by means of DFT and QTAIM, in order to better understand their properties at the molecular level. Sub-cells of type I hydrates were modeled as independent rigid cages, both empty and containing guest molecules. Interaction potentials of guest molecules inside each cage, and moving from a cell to the adjacent one, were calculated using the DFT approximation B3LYP/6-311+g(d, p), considering the cases with and without long range Coulombic corrections. The selected theory level was validated by comparison of the simulated Raman spectra with the experimental ones, for the case of type I lattice at full occupation of CO2 and CH4, respectively. For this comparison, Fermi resonances of CO2 were taken into account by transforming experimental bands to the corresponding theoretical non-mixed states. On the one hand, our results confirm the validity of the theory level selected for the model. We have shown the high anisotropy of the guest–cell interaction potential of the molecules analyzed, which has implications in the formulation and use of equations of state, and in the study of transport properties as well. On the other hand, our results suggest that the concentration of guest species inside type I hydrates could be computed from the comparison of experimental and predicted Raman spectra, although there are non-trivial experimental limitations to get over for that purpose.